Technopreneur: Small Business Empowerment for South Coast in Malang, Indonesia - Agustin, Yuli; Wijijayanti, Trisetia; Winarno, Agung; Siswanto, Ely; Narmaditya, Bagus Shandy (International Journal of Psychosocial Rehabilitation, 2020)
This study is aimed at examining the technopreneurship of Micro, Small and Medium Enterprises (MSMEs) in Malang, Indonesia. As one of the aspects of the national economy, the region plays an active role in the development of MSME, which faces both internal and external problems. This study used descriptive qualitative to develop theories that are built through data obtained in the field. By identifying the ef ective strategy of addressing weaknesses in production, this study helps MSMEs to find the right strategies, policies, and programs for business development. The findings showed that technopreneurs had not been clearly identified in terms of number and line of business due to inadequate understanding, knowledge, and information for related agencies conducting data collection for MSMEs used in categorization. The lack of information related to the progress of science and technology hinders the development of facilities and infrastructure and does not support business progress.